Assemblage structure and distribution of fish larvae on the North Kenya Banks during the Southeast Monsoon season. (15th October 2021) - Mwaluma, James; Ngisiang'e, Noah; Osore, Melckzedeck; Kamau, Joseph; Ong'anda, Harrison; Kilonzi, Joseph; Roberts, Mike; Popova, Ekatarina; Painter, Stuart C.
Abstract: The North Kenya Banks (NKB) is the broadest area of continental shelf along the Kenyan coast, and experiences higher productivity relative to neighbouring shelf regions. It is an area of great importance to Kenya with new emerging fisheries that have the potential to improve the livelihoods of local impoverished fishing communities. Managing these emerging fisheries successfully however is challenged by insufficient data on the fisheries and the local marine environment, and the lack of a management plan specifically for the NKB region. Here, baseline information on the ichthyoplankton assemblage across the NKB region during the Southeast Monsoon season is described and analysed to understand the effect biophysical parameters have on larval composition, abundance and distribution. The dominant fish larvae families were Engraulidae (29.5% of total) followed by Sphyraenidae (8.6%), Carangidae (8.2%), Scombridae (6.2%) and Lutjanidae (5.5%), whilst the dominant species within these families were Encrasicholina sp., Sphyraena sp., Thunnus albacares, T. alalunga and Lutjanus sp., respectively. A high prevalence of larvae from migratory species such as T. albacares, T. alalunga and Gempylus serpens was found across the northern part of the NKB, suggesting that the area may be an important nursery area for migratory fish with implications for fisheries across the wider Western Indian Ocean. Zooplankton abundance, temperature and conductivity played a positive role in determining the structure and composition of fish larvae assemblages across the NKB region. The high larval densities encountered out to the shelf break (200 m contour) imply that the NKB is a productive fishery and as such requires appropriate management oversight. Furthermore, the identification of a clear influence by temperature on larval distributions suggests that the NKB fishery may be susceptible to predicted future warming in this region with implications for both management of the resource and those fishing communities who benefit from the fisheries. Highlights: Synoptic study of fish larvae distributions across the North Kenya Banks. Important breeding and nursery grounds for migratory and native fish identified. Biophysical variables affect fish larvae abundance and distribution.